If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1p = 6 + -2(p + 5) Reorder the terms: 2 + -1p = 6 + -2(5 + p) 2 + -1p = 6 + (5 * -2 + p * -2) 2 + -1p = 6 + (-10 + -2p) Combine like terms: 6 + -10 = -4 2 + -1p = -4 + -2p Solving 2 + -1p = -4 + -2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2p' to each side of the equation. 2 + -1p + 2p = -4 + -2p + 2p Combine like terms: -1p + 2p = 1p 2 + 1p = -4 + -2p + 2p Combine like terms: -2p + 2p = 0 2 + 1p = -4 + 0 2 + 1p = -4 Add '-2' to each side of the equation. 2 + -2 + 1p = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 1p = -4 + -2 1p = -4 + -2 Combine like terms: -4 + -2 = -6 1p = -6 Divide each side by '1'. p = -6 Simplifying p = -6
| -5v-28=8(v+3) | | 5g+3+2g=7g+15 | | x/1=-34+24 | | 6x-3=2x-11 | | Z+3=-6 | | 2-12=z/-5 | | 7v-43=5(v-7) | | 7x-3x+3+7=26 | | 2(-8k+6)=12 | | x^2+x-8=2x | | 13x+4=18x-8 | | 9x-25=88 | | 3w-6w=24 | | 15x^2+34+15= | | 8x+8=9x-3 | | 6+3x=-x-6 | | y=-0.0002x^2+20x | | -30=-6v+3(v-2) | | 3x-1=1x+13 | | y=7x+0.4 | | 2xw=14 | | -4/3/(-8/9) | | x+2x+3x-6=12 | | -5b=-3b+-2b+-20 | | 5x+21/10=x/10 | | 8(w-8)=-8w-48 | | x+3x-7=13 | | j+45=79.50 | | 2(5x-8)+=-4x-13 | | x^3-7x+10x=0 | | 3.8x-3=2.8x | | -8m=-7m+-3 |